The legal and regulatory framework for establishing and accompanying small enterprises in Algeria - BOUDELIOU, Salim; KELLOU, Hichem (Journal of Human Sciences, 2020)
The study examines the legal and regulatory Framework for establishing and accompanying Small enterprise’s in Algeria as institutions That have a role in the economic development of the country. Effective in the overall development of Algeria.